Phonological Interference in English Pronunciation Produced by Students at Senior High School (A Case Study of Buginese and Javanese Students) - Nirwana Nirwana; Suhono Suhono (Anglophile Journal, 2023)
This research discussed the Buginese and Javanese phonological interference and the factors that influenced that case from the students in senior high school. The method that was used in this research was qualitative research. The researchers collected the data with nine fricative consonants (f, v, θ, ð, s, z, ʃ, ʒ, h) by reading test, recording and interview, then analyzed with the theory by Weinreich (1979). The object was the Buginese and Javanese students of Senior High School 2 of East Luwu. The data showed that phonological interference produced by Buginese and Javanese are only two of three kinds of phonological interference by Crystal (2003). From Buginese students, the researchers only found one category of phonological interference which was sound replacements on consonant {f}, meanwhile on Javanese students found two categories of phonological interference, that were sound addition on sound {h} and sound replacement on sound ʃ. On the other hand, there are two factors that caused phonological interference of Buginese and Javanese students in this research, such as bilingual background and disloyalty to the target language. The factors that were found related to the factors mentioned by Weinreich (1979). Keywords: Phonological Interference, Buginese Phonological Interference, Javanese Phonological Interference